Auctions for public construction with corner-cutting - Kenju Akai; Tatsuyoshi Saijo; Shigehiro Serizawa (Osaka University, Institute of Social and Economic Research (ISER), 2009)
This paper reports the theoretical and experimental results of auctions for public construction in which firms cut corners. We show that winning bids and qualities of the constructed buildings are both zero in equilibria if there are at least two firms whose initial cash balances are zero. The experimental results support that firms with zeroinitial cash balance win and that the winning bids and the qualities of the constructed buildings are considerably low.
Keywords: C92; D44; L15; 330; Corner-cutting; Public procurement; First-price auction; Experiment